Multistage aqueous two‐phase extraction of a monoclonal antibody from cell supernatant. (29th April 2015) - Muendges, Jan; Zalesko, Alexej; Górak, Andrzej; Zeiner, Tim
<x xml:space="preserve">Abstract</x> This article presents results of continuous multistage aqueous two‐phase extraction of an immunoglobulin G1 from cell supernatant in a mixer‐settler unit. An aqueous two‐phase system consisting of polyethylene glycol 2000, phosphate salt, and water was applied without and with sodium chloride (NaCl). Influences of different parameters such as throughput, phase ratio, and stage number on the extraction performance were analyzed. For systems without NaCl, the extraction was carried out as a washing step. An increase of stage number from one to five stages enabled to increase the immunoglobulin G1 purity from 11.8 to 32.6% at a yield of nearly 90%. Furthermore, a reduction of product phase volume due to a higher phase ratio led to an increase of purity from 20.8 to 29.6% in a three‐stage countercurrent extraction. For experiments with NaCl moderate partitioning conditions were adjusted by adding 8 wt% NaCl. In that case, the extraction was carried out as a stripping step. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:925–936, 2015